THU0390 Patients with systemic sclerosis develop focal fibrosis over time, and increased ecv diffuse fibrosis seen in poor prognostic group – a first longitudinal cardiac mri study. (12th June 2018) - Dumitru, R.B.; Bissell, L.-A.; Erhayiem, B.; Fent, G.; Hensor, E.M.; Giollo, A.; Kidambi, A.; Greenwood, J.; Del Galdo, F.; Plein, S.; Buch, M.H.
Abstract : Background: Subclinical SSc-cardiomyopathy is described in up to 2/3 of the patients when sensitive methods such as cardiac MRI(CMR) are used. The prognostic implications and the natural history of these findings is unknown. Objectives: To evaluate in SSc patients, free of cardiovascular (CV) risk factors and CV disease (CVD) the prevalence, clinical association and natural history of CMR abnormalities over 3 years. Methods: 35 SSc patients, fulfilling the ACR/EULAR criteria, with no CVD, diabetes and ≤1 CV risk factor had 2 CMRs, 3 years apart. A 3T CMR with late gadolinium enhancement (LGE), T1 mapping for extracellular volume (ECV) quantification and stress perfusion(data available later)was undertaken. Initial CMR was compared with CMR results of 30 healthy controls(HC). Results: 35 pts had an initial CMR:26(74%) female, mean(SD) age 55(, 13 15 (43%) dcSSc, 11 (31%) ACA+, 12 (34%) Scl70+, 15 with(43%) interstitial lung disease(ILD) and 13 (37%) with history of digital ulcers(DU). 21 (60%) received any DMARD over the 3 year period and 10 (29%) prior treatment with cyclophosphamide. The first CMR(CMR1) of SSc pts vs HC showed higher ECV% values and comparable left ventricle(LV) volumes(table 1). LGE was present in 9/22 pts vs 1/30 HC. 22/35 pts had a second CMR (CMR2) at year 3(Y3). A further 5 pts had evidence of LGE, total of 14 (40%): 7/14 had dcSSc, 6/14 males, 2 ACA positive, 6 Scl70 positive. LGE distributed in the basal and mid segments, mainly in a linear or patchy pattern. Of those with LGE at CMR1 (5/9 pts with LGE on CMR1 had CMR2) no change in the LGE pattern at CMR2 was observed. None of the initial CMR measures associated with LGE development at Y3 (p>0.05). Whilst ECV had an overall decrease, ECV incresed in patients with ILD [mean diff.(CI) 3 (-1, 6), p=0.14]and in those with higher mRSS at baseline(r=0.455, p=0.04). A significant decrease over the 3 years was observed in LV end-diastolic volume (LVEDV/BSA), LV end-systolic volume(LVESV/BSA) and left ventricular stroke volume (LVSV/BSA) (table 1). A decrease in LVEDV/BSA was noticed for those with a history of DU[mean diff.(CI) −5(−12, 2), p=0.1], ILD[mean diff.(CI) −6(−12, 0.5), p=0.07)]and shorter disease duration(r=-0.504, p=0.02). Conclusions: This longitudinal CMR study in SSc demonstrates that CMR is sensitive to change over time. More individuals developed LGE (of focal fibrosis) despite immunosuppressive treatment, and ECV% (diffuse fibrosis) appeared to worsen in a poor prognostic group. Functional changes were also observed. These data justify larger studies to inform stratification strategy for CMR in SSc, and also provide new insights for further investigation. Disclosure of Interest: None declared